Live-cell imaging uncovers the relationship between histone acetylation, RNA polymerase II phosphorylation, transcription, and chromatin dynamics - Saxton, Matthew Neeley, author; Stasevich, Timothy J., advisor; Nishimura, Erin O., committee member; Hansen, Jeffrey, committee member; Krapf, Diego, committee member (Colorado State University. Libraries, 2023)
Living cells are capable of turning a one dimensional strand of nucleic acids into a functional polypeptide. A host of steps and factors are involved in the process of transcription and translation, and understanding each of them is necessary for comprehending and characterizing life. While new technologies and assays have expanded our understanding of eukaryotic transcription, there is still much to be learned. In particular, single-molecule microscopy provides a powerful and versatile platform for studying the genesis of RNA with unparalleled spatiotemporal resolution (Chapter 1). First, we characterize the timing, kinetics, and occupancy of phosphorylated RNA polymerase II (RNAP2) using a single-copy HIV-1 reporter system. This work provides strong evidence for clusters of phosphorylated, initiating RNAP2 which is spatially separated from bursty, downstream RNA synthesis. It is found that RNAP2-Ser5-phosphorylation (Ser5ph) precedes RNA output by ~1 minute, and RNAP2 arrives at the locus in a phosphorylated state (Chapter 2). Then, we examine the spatial correlation between H3K27 acetylation and Ser5ph in living cells on the course of minutes to hours. Contrary to expectations based upon ChIP data, we find that the two signals are in fact spatially separated. This argues for a functional separation between transcriptional poising and initiation, likely aiding bursty behavior. Next, the dynamics of single chromatin-incorporated nucleosomes in the context of H3K27 acetylation and transcription initiation is determined with super-resolution single-molecule imaging. The physical movement of chromatin inside of H3K27ac and RNAP2-Ser5ph enriched regions is found to be significantly different, despite both marks being traditionally associated with transcriptionally active chromatin. (Chapter 3). Much of this work utilizes bead-loading in order to introduce proteins and DNA into living cells. A simple, effective, and cheap procedure, bead-loading is a highly effective and versatile technique that is generally underutilized. To facilitate communication of this process, a detailed protocol is included (Chapter 4). While this culmination of work furthers our understanding of cellular genetic expression and eukaryotic transcription, it also introduces many new questions that are promising areas of study. Fortunately, the combination of imaging technology and knowledge developed here provides promising new fronts for studying transcription in living cells (Chapter 5).
Keywords: H3K27ac; single molecule tracking; chromatin; transcription; histone modifications